The potential of local microalgae isolates in biotechnological applications - Azhan, Nik Airin Syazlin; Abdullah, Mohammad Faiz Foong; Abd Hamid, Umi Marshida; Mohamad Jamil, Norashirene; Abdul-Aziz, Aziyah (Faculty of Applied Sciences, 2025)
Microalgae biofilms have emerged as a promising candidate in biotechnology, including enhancing biomass production for various applications and as an efficient alternative to conventional wastewater treatment. This study explores the potential of local microalgae in reducing pollutants in wastewater by sequestering nitrogen and phosphorus while generating biomass that can be used for human food and animal feed. Local microalgal isolates are known to have potential in offering cost-effective, efficient, and sustainable nutrient removal while enabling resource recovery and minimizing ecological risks in wastewater treatment. A total of eight microalgal biofilm samples were successfully isolated and preliminary identified. Three were from the Chlorophyta group, one was Cyanobacteria while the other belonged to the Ochrophyta group. Highest biomass yield was produced by isolate MA12 at a 90.0% increase in wet weight mg/L, followed by 76.9% and 70.0% by MA22 and MA19, respectively. When grown in synthetic wastewater for seven days, the highest reduction in TN was observed in MA18 at 43.5% while MA7 showed a remarkable performance of 95.0% of reduction of TP. Integrating microalgae biofilms into wastewater treatment systems can thus enhance pollutant removal and contribute to the circular economy by converting waste into valuable bioproducts. This study highlights the novelty of using local microalgae isolates both in environmental protection and resource recovery, paving the way for their implementation in sustainable wastewater management practices.